Prevalence and Risk Factors of Emotional Mental Disorder Among University Students: A Cross-Sectional Study (Jurnal Psikologi Integratif, 2025)
Emotional mental health issues among university students have shown an increasing trend over time, reaching concerning levels when compared to the general population. Early detection is very important for the university as an early intervention to improve students’ mental health. This study used an analytic observational design with a cross-sectional approach. A total of 1564 students from 10 faculties of Sriwijaya University filled in the SRQ-29 questionnaire online via social media from January 2020 – 27 August 2020.  The obtained data were analyzed using the Mann Whitney, Chi-Square, and Binary Logistic Regression Test with a significance value of p